Adenine suppresses IgE-mediated mast cell activation. Issue 2 (June 2015) - Silwal, Prashanta; Shin, Keuna; Choi, Seulgi; Kang, Seong Wook; Park, Jin Bong; Lee, Hyang-Joo; Koo, Suk-Jin; Chung, Kun-Hoe; Namgung, Uk; Lim, Kyu; Heo, Jun-Young; Park, Jong Il; et al.
Abstract: Nucleobase adenine is produced by dividing human lymphoblasts mainly from polyamine synthesis and inhibits immunological functions of lymphocytes. We investigated the anti-allergic effect of adenine on IgE-mediated mast cell activation in vitro and passive cutaneous anaphylaxis (PCA) in mice. Intraperitoneal injection of adenine to IgE-sensitized mice attenuated IgE-mediated PCA reaction in a dose dependent manner, resulting in a median effective concentration of 4.21 mg/kg. In mast cell cultures, only adenine among cytosine, adenine, adenosine, ADP and ATP dose-dependently suppressed FcɛRI (a high affinity receptor for IgE)-mediated degranulation with a median inhibitory concentration of 1.6 mM. It also blocked the production of LTB4, an inflammatory lipid mediator, and inflammatory cytokines TNF-α and IL-4. In addition, adenine blocked thapsigargin-induced degranulation which is FcɛRI-independent but shares FcɛRI-dependent signaling events. Adenine inhibited the phosphorylation of signaling molecules important to FcɛRI-mediated allergic reactions such as Syk, PLCγ2, Gab2, Akt, and mitogen activated protein kinases ERK and JNK. From this result, we report for the first time that adenine inhibits PCA in mice and allergic reaction by inhibiting FcɛRI-mediated signaling events in mast cells. Therefore, adenine may be useful for the treatment of mast cell-mediated allergic diseases. Also, the upregulation of adenine production may provide another mechanism for suppressing mast cell activity especially at inflammatory sites.